A direct link between chorus emissions and pulsating aurora on timescales from milliseconds to minutes: A case study at subauroral latitudes. Issue 11 (27th November 2015) - Ozaki, Mitsunori; Yagitani, Satoshi; Sawai, Kaoru; Shiokawa, Kazuo; Miyoshi, Yoshizumi; Kataoka, Ryuho; Ieda, Akimasa; Ebihara, Yusuke; Connors, Martin; Schofield, Ian; Katoh, Yuto; Otsuka, Yuichi; et al.
Abstract: A correlation was observed between chorus emissions and pulsating aurora (PA) from observations at Athabasca ( L ≈4.3) in Canada at 9:00–9:20 UT on 7 February 2013, using an electron multiplying charge‐coupled device camera and a VLF loop antenna with sampling rates of 110 Hz and 100 kHz, respectively. Pulsating aurora having a quasiperiodic variation in luminosity and a few hertz modulation was observed together with chorus emissions consisting of a group of successive rising‐tone elements. The repetition period and modulation frequency of the PA are in good agreement with those of the modulated chorus. After 9:11 UT, the temporal features of the aurora became aperiodic PA of indistinct modulation. Simultaneously, the rising‐tone chorus turned into chorus emissions consisting of numerous rising‐tone elements. The equatorial geomagnetic field inhomogeneity calculated using the Tsyganenko 2002 model shows a decreasing trend during the period. This result is consistent with nonlinear wave growth theory having a small geomagnetic field inhomogeneity, which contributes to a decrease in the threshold amplitude to trigger discrete chorus elements. These observations show a close connection between chorus emissions and PA on timescales from milliseconds for generation of discrete chorus elements on the microphysics of wave‐particle interaction to minutes for the variations of the geomagnetic field inhomogeneity related with the substorm activity. Key Points: A direct link between discrete chorus elements and PA was observed The temporal features of discrete chorus elements were related to PA The magnetic field inhomogeneity plays a crucial role in the generation of PA